Microflows and Nanoflows Fundamentals and Simulation - Karniadakis, George; Beskok, Ali.; Aluru, Narayan; Antman, S.S.; Marsden, J.E.; Sirovich, L.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
In the last few years there has been significant progress in the development of microfluidics and nanofluidics at the application as well as at the fundamental and simulation levels. This book provides a comprehensive summary of these changes describing fluid flow in micro and nano configurations. Where as in their previous book entitled Microflows: Fundamentals and Simulation the authors covered scales from one hundred nanometers to microns (and beyond), in this new book they discuss length scales from angstroms to microns (and beyond). While still maintaining the emphasis on fundamental concepts with a mix of semianalytical, experimental, and numerical results, this book outlines their relevance to modeling and analyzing functional devices. The text has been divided into three main subject categories: gas flows; liquid flows; and simulation techniques .The majority of the completely new developments in this book are in liquid flows and simulation techniques chapters with modified information throughout the rest of the book. This book can be used in a two-semester graduate course. Also, selected chapters can be used for a short course or an undergraduate-level course. The book is suitable for graduate students and researchers in fluid mechanics, physics, and in electrical, mechanical and chemical engineering. Review of earlier volume on Microflows from the European Journal of Mechanics B/Fluids, 2002: "For those who want to compute flows at the micro scale, this monograph is a must. It describes the state of the art and helps by providing the coefficients, such as needed in situations of slip. Those who wonder what new fluid dynamics there is in the microworld are served by the overview of theory and treasures of numerical methods.".
Gas Flows -- Governing Equations and Slip Models -- Shear-Driven Flows -- Pressure-Driven Flows -- Thermal Effects in Microscales -- Prototype Applications of Gas Flows -- Basic Concepts and Technologies -- Liquid Flows -- Electrokinetic Flows -- Surface Tension-Driven Flows -- Mixers and Chaotic Advection -- Simple Fluids in Nanochannels -- Water in Nanochannels -- Electroosmotic Flow in Nanochannels -- Functional Fluids and Functionalized Nanotubes -- Simulation Techniques -- Numerical Methods for Continuum Simulation -- Multiscale Modeling of Gas Flows -- Multiscale Modeling of Liquid Flows -- Reduced-Order Modeling -- Reduced-Order Simulation.
Keywords: Mathematics; Computer mathematics; Fluids; Fluid mechanics; Mechanical engineering; Electronics; Microelectronics; Nanotechnology; Mathematics; Computational Mathematics and Numerical Analysis; Fluid- and Aerodynamics; Engineering Fluid Dynamics; Nanotechnology; Mechanical Engineering; Electronics and Microelectronics, Instrumentation; Electronic books